Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 13882 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Zosterops japonicus", "HasGeospatialIssue is false", "Geometry POLYGON((-157.24 18.38,-157.24 20.45,-153.79 20.45,-153.79 18.38,-157.24 18.38))" ] } The dataset includes 13882 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002945-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences